Pricing Analysis of Online Shopping Platforms Considering Consumer Information Levels - Chen, Hao; Xiong, Weiqing; Xiong, Peichen (Frontiers in Psychology, 2022)
To address the problem of frequent dishonest transactions by online shopping platform merchants, we developed monopoly and competitive platform pricing models, based on two-sided market theory, that introduce consumer information levels. This article analyzes the incentives of the platforms to improve consumer information levels in the platform pricing strategies. Monopoly online shopping platforms aim to maximize profits. The higher the consumer information level is, the lower the fees charged to merchants—this can lead to increased platform profits. The charging of consumers depends on cross-network externalities. Competitive online shopping platforms also aim at maximizing profits. Under the circumstance that the number of consumers remains the same, the higher that the consumer information level is, the more merchants the platforms will attract. This reduces bilateral user fees and platform profits will be lower. From the perspective of the consumer information level, the paper analyzes the impact of monopoly and competitive platforms adopting return measures to improve the level of consumer information on platform pricing, the number of bilateral users, and profits.